Hydrogen oxidation on ordered intermetallic electrodes covered with CO - Innocente, A. F. [UNESP]; Angelo, A. C. D. [UNESP] (Elsevier B.V., 2008)
This describes an experimental evaluation of the electrocatalytic activity of the hydrogen oxidation reaction on electrodes of platinum and the ordered intermetallic phases PtSb and PtSn, on which CO has previously been deposited. The experiments were carried out in perchloric acid solution and the analysis based on steady-state polarization curves and Tafel plots derived from chronoamperometric data. Both intermetallics, PtSb and PtSn, performed better than Pt towards the HOR, when their surface was deliberately covered with CO. It is suggested that the intermetallic surfaces have a lower affinity for CO molecules, causing a lower CO coverage on these surfaces, and/or a weaker surface-CO interaction, compared to Pt under the same conditions. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: ordered intermetallic materials; CO adsorption; electrocatalysis; hydrogen oxidation